Motivasi Intrinsik dengan Prokrastinasi Akademik Pada Mahasiswa Himpunan Mahasiswa Islam (HMI) - Widiarti Widiarti; Ahmad Muhammad Diponegoro (Universitas Ahmad Dahlan, 2021)
Intrinsic Motivation with Student Academic Procrastination at the Islamic Student Association (HMI)The background of this research is the high academic procrastination of students at the Islamic Student Association (HMI). This study aims to determine the relationship between Intrinsic Motivation and Academic Procrastination. This research is a quantitative research with a correlational research design. The research population was 64 students, the sample was taken using a saturated sampling technique. Collecting data using a Likert scale method based on aspects of intrinsic motivation and the characteristics of academic procrastination. The data analysis technique used simple regression with the help of the SPSS version 21 application. The results of the analysis showed the value of the correlation coefficient r = 0.413 with (p) = 0.001 <0.05. This shows that intrinsic motivation has a significant relationship with academic procrastination in the Islamic Student Association (HMI). The value of r square of 0.171 indicates that the intrinsic motivation variable has an influence on the academic procrastination variable of 17.1%.